Predictors of psychiatric readmissions in the short- and long-term: a population-based study in Taiwan (Clinics, 2010)
OBJECTIVES: To explore the risks and rates of readmission and their predictors 14 days, one year, and five years after discharge for the psychiatric population in Taiwan. METHODS: This was a prospective study based on claims from 44,237 first-time hospitalized psychiatric patients discharged in 2000, who were followed for up to five years after discharge. The cumulative incidence and incidence density of readmission were calculated for various follow-up periods after discharge, and Cox proportional hazard models were generated to identify the significant predictors for psychiatric readmission. RESULTS: The less than 14-day, one-year, and five-year cumulative incidences were estimated at 6.1%, 22.3%, and 37.8%, respectively. The corresponding figures for incidence density were 4.58, 1.04, and 0.69 per 1,000 person-days, respectively. Certain factors were significantly associated with increased risk of readmission irrespective of the length of follow-up, including male gender, length of hospital stay >;15 days, economic poverty, a leading discharge diagnosis of schizophrenia/affective disorders, and residence in less-urbanized regions. Compared to children/adolescents, young adults (20-39 years) were significantly associated with increased risks of